The Influence of Motivation, Work Environment and Productivity on the Performance of Health Personnel - Mulyani, Sri; WA, Armalia Reny; Hasbullah, Hasbullah; Alie, Maria Septijantini; Desmon, Desmon; Indriyani, Susi (Indonesian Journal of Global Health Research, 2024)
Human Resources (HR) is a very important element in an institution. Factors that influence performance include discipline and skills, motivation, situational factors and system or work environment factors, work experience and productivity. The aim of this research is to determine the influence of motivation, work environment and productivity on the performance of Kangkung II Kendal Public Health Center employees. The method used in this research was descriptive quantitative, the number of samples used was 45 respondents from the total population using the total saturation technique at the Kangkung II Community Health Center. The research results showed that the three variables of motivation, work environment and productivity had a simultaneously positive effect on employee performance at the Kangkung II Kendal Community Health Center. The results of the motivation variable partially have a positive effect on the performance of Kangkung II Community Health Center employees. The results of the work environment variable partially have a positive effect on the performance of the Kangkung II Kendal Public Health Center employees. The results of the productivity variable partially have a positive effect on the performance of the Kangkung II Kendal Public Health Center employees. Suggestions are expected to use other independent variables, for example education, work discipline, work ethic, wages, leadership, workload and so on.